1992
DOI: 10.1007/bf02540561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic interesterification on the melting point of tallow‐rapeseed oil (LEAR) mixture

Abstract: To reduce the melting point of a tallow-rapeseed oil mixture, the triglyceride composition of the mixture was altered by enzymatic interesterification in a solvent-free system. The interesterification and hydrolysis were followed by melting point profiles and by free fatty acid determinations. The degree of hydrolysis was linearly related to the initial water content of the reaction mixture. The rate of the interesterification reaction was influenced by the amount of enzyme but not much by temperature between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
38
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 11 publications
7
38
0
1
Order By: Relevance
“…It was found that the higher the amount of water in the reaction system, the higher the FFA and MAG + DAG contents and the smaller the TAG content. Such conclusion is in agreement with the findings of other authors (Foglia et al, 1993, Forssell et al, 1992, Ledochowska and Wilczynska, 1998 studying the enzymatic interesterification of tallow + vegetable oil systems. There are reports (Ledochowska and Wilczynska, 1998, Ledochowska and Datta, 1998, Mohamed et al, 1993 that the percentage of MAG in enzymatically interesterified fats is low (~1%) because MAG are reactive and rapidly undergo esterification.…”
supporting
confidence: 94%
“…It was found that the higher the amount of water in the reaction system, the higher the FFA and MAG + DAG contents and the smaller the TAG content. Such conclusion is in agreement with the findings of other authors (Foglia et al, 1993, Forssell et al, 1992, Ledochowska and Wilczynska, 1998 studying the enzymatic interesterification of tallow + vegetable oil systems. There are reports (Ledochowska and Wilczynska, 1998, Ledochowska and Datta, 1998, Mohamed et al, 1993 that the percentage of MAG in enzymatically interesterified fats is low (~1%) because MAG are reactive and rapidly undergo esterification.…”
supporting
confidence: 94%
“…Some examples reported recently include the transesterification of tallow with sunflower, soybean [9], rapeseed oil [10], and canolapalm oil mixtures [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to chemical methods, enzymatic synthesis as a tool for fat modification has many advantages. Catalyzed with lipases, interesterification reactions can be directed in controlled ways, and specific or totally new products can be produced [4]. Microbial lipases have a great potential for commercial application due to their stability, selectivity and broad substrate specificity.…”
Section: Introductionmentioning
confidence: 99%